Strategic positioning of carbon fiber layers in an UHMwPE ballistic hybrid composite panel - Zulkifli, Faiz (2021)
The effects of inter-ply stacking sequences on the ballistic and structural performance of ultra-high molecular weight polyethylene (UHMwPE) fiber/carbon fiber hybrid composite hard ballistic panels have been studied. Unexpected effects were observed simply by varying the positions of small amounts of carbon layers at the front, middle, back and front-back of the UHMwPE-based panels. The most dramatic positive hybrid effect was observed for a front-facing hybrid configuration resulting in a significant 30% reduction in back-face signature (BFS) with a more than two times improvement in flexural yield strength. Interesting secondary hybrid effects such as the mitigation of bulging and buckling of the UHMwPE component of the panel as well as bullet deformation upon ballistic impact by the carbon layer was observed. These results indicate that strategic positioning of the carbon layer in UHMwPE panels can boost the ballistic performance of applications where low BFS and structural performances are key.